Kinetics of Complexation of Ni(II) with N,N´ -Ethylene disalicylamide in Alkaline Media and Effect of Cationic Surfactant on the Rate of Reaction - Nayak, B.; Bhattimisra, S.D. (Asian Journal of Chemistry, 2010)
The kinetics of formation reaction of N,N´-ethylene disalicylamidato nickelate(II) is followed at 30ºC in alkaline media. A bellshaped pH-rate profile is obtained indicating a maximum at pH = 9.5. The active species near the maximum are the hydrated Ni(II) species and the deprotonated species of the ligand. The rate constant for formation decreases with increase in concentration of cetyl trimethyl ammonium bromide (CTAB). This results from partitioning of the hydrophobic ligand in the micellar pseudophase and electrostatic repulsion between the metal and the micellar surface.